Newspaper framing of 2014 ebola outbreak in Nigeria: Assessing the nexus between audience perceptions and message influence / Adelakun Lateef Adekunle - Adelakun Lateef, Adekunle (2017)
Having examined series of studies on media framing of health issues, a knowledge gap was noticed. Perhaps because framing of issues involves more than just the media but also other players most especially the audience, it has been very difficult to integrate the frames in media reports of a health outbreak with the framing influence on audience perceptions of and reactions to the issue framed all in just one study. The challenge has been complex theoretical explanations as well as methodological approaches involved. This study therefore employed triangulation approach in theoretical underpinning, methods of data gathering, and methods of data analyses. The approach was required to verify the media framing of Ebola outbreak in Nigeria in one hand and the audience perceptions and reactions towards the framed Ebola reports on the other hand. Discussions on the central focus of this study were grounded on some media effects theories, which explain media-audience relationship on the premises of message influence. The theories, agenda-setting, framing and priming were, based on their interrelated and complementary postulations, used to explain the layers in media-audience relationship process. Through content analysis of two daily newspapers reports of Ebola during the outbreak in Nigeria, this study established the framing patterns employed while reporting the outbreak as well as the preponderant frames used. Ten frames were found prominently emphasised in the reports while two (containment and fatality frames) were made salience in almost half of the total reports on the outbreak. The outcome was used to justify the priority upheld between the competing newspapers interests to sell and the media social responsibility towards containing the outbreak. The much capitalisation on containment frame portrayed the newspapers purposive interest to free the society of the outbreak, a reflection of the media social responsibility role. The priority, which pose no threat to professional journalism was not only much appraised but also recommended for media involvements in all health crises. This finding was not only confirmed but also extended further by opinion survey of 400 newspaper audience. The survey, which was quantitatively analysed through SmartPLS confirmed a significant relationship between the framed newspaper reports of and the audience perceptions and reactions to the outbreak. It further established that audience exposure to and audience perceptions of the framed health reports are significant factors of the change in audience behaviours towards the outbreak. Based on some limitations in the scope as well as methodological approaches, this study therefore recommended that future studies engage holistic perspectives towards studying health outbreaks.